Analysis of space charge and charge trap characteristics of gamma irradiated silicone rubber nanocomposites. Issue 2 (20th April 2020) - Thangabalan, Baskar; Sarathi, Ramanujam; Harid, Noureddine; Griffiths, Huw
Abstract : Silicone rubber is widely used for electrical insulation and may be exposed to a harsh environment. The present study envisaged to improve insulation properties of silicone rubber by adding an optimised quantity of nanofillers. The fundamental space charge and charge trap characteristics were studied by adopting the pulsed electroacoustic analysis technique and through surface potential measurement. The dielectric properties of the materials were analysed through measurement of permittivity and loss factor of the material at different frequencies and temperatures. The influence of gamma irradiation on variations in fundamental properties of the material was characterised. The results of the study indicate that 5 wt.% alumina added nanocomposites had better space charge performance under gamma irradiation compared with virgin silicone rubber.